Higher Education Ambitions and Societal Expectations - Béatrice Cabau (Athens Institute for Education and Research, 2014)
In 2004, i.e. seven years after the retrocession of Hong Kong to the People's Republic of China (PRC), the then Chief Executive aimed to promote the former British colony as 'Asia's world city'. The same year, the University Grants Committee echoed this ambition by envisaging the Hong Kong Special Administrative Region (HKSAR) as becoming an 'education hub' in the region with the main objective of attracting international students for study and work. A few years later, education services were designed as one of the six industries able to propel Hong Kong towards a knowledge-based economy. This paper aims to illustrate the challenges of the former British colony to acquire a strong local academic identity and profile to answer the needs of a knowledge-based society driven by globalisation. These challenges will be scrutinised in the interlinked perspectives of the concepts of higher education (HE) hub and internationalisation of the HE sector in Hong Kong, illuminating local, regional and global concerns. The main conclusion is that one of the biggest challenges is to strike a balance between forces of globalisation and their consequences upon the Hong Kong community's needs and enhancing ties with the PRC as stated in the HKSAR policy. So the balance is to be found between (national) convergence and (international/global) engagement. This profile has repercussions for implementing a HE internationalisation policy anywhere in the world.